El-Shadday dan Korelasinya dengan Dewi Karema dalam Mitologi Penciptaan Manusia Di Suku Minahasa - Firman Panjaitan; Regen Wantalangi (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2021)
Understanding of God is very important in religious life, especially when religion is confronted with culture. There needs to be contextualization efforts in understanding God comprehensively so that it can be accepted from a religious as well as cultural perspective. Through this, God is not only understood correctly Biblically, but at the same time is understood based on the context of the local community. This article aims to find the understanding of God in the Minahasa context by contextualizing the understanding of God in the Bible with the local context. This article uses a qualitative method with a literature study approach for research into the Minahasa cultural context coupled with a critical interpretation of biblical research, especially Genesis 1:26-28. The results of the study prove that God, known as El Shadday in the Bible understanding can be contextualized with the understanding of Dewi Karema, so that God in the form of El Shadday understood by Minahasa culture is not just a masculine God but also a feminine God. Thus the God of El Shadday in the Bible is not a foreign God in the life of the Minahasa tribe, but a God who is very close to human life, especially in the figure of Dewi Karema. Pemahaman tentang Allah menjadi hal yang sangat utama dalam kehidupan beragama, terutama ketika agama diperhadapkan pada budaya. Perlu ada upaya kontekstualisasi dalam memahami Allah secara komprehensif sehingga dapat diterima dalam perspektif agama sekaligus budaya. Melalui hal ini, Allah tidak hanya dipahami dengan benar secara Alkitabiah, tetapi sekaligus dipahami berdasarkan konteks masyarakat setempat. Artikel ini bertujuan untuk menemukan pemahaman Allah dalam konteks Minahasa dengan cara mengkontekstualisasikan pemahaman tentang Allah dalam Alkitab dengan konteks setempat. Artikel ini menggunakan metode kualitatif dengan pendekatan studi literatur bagi penelitian terhadap konteks budaya Minahasa ditambah dengan tafsir kritis terhadap penelitian Alkitab, khususnya Kejadian 1:26-28. Hasil penelitian menunjukkan bahwa Allah, yang dikenal dengan nama El Shadday dalam pemahaman Alkitab dapat dikontekstualisasikan dengan pemahaman Dewi Karema, sehingga Allah dalam wujud El Shadday yang dipahami oleh budaya Minahasa bukan sekadar Allah yang maskulin melainkan Allah dalam wujud feminine, sehingga kehidupan El Shadday sangat dekat dengan kehidupan manusia.